“I have read and accept the terms of use”: User assistance initiatives in the midst of what may be one of the biggest lies on the internet - Picalho, Antonio Carlos; de Oliveira Lucas, Elaine Rosangela (AWARI, 2022)
Terms of use are documents about your rights and obligations when using digital products and services. They may have other names, such as terms of service or privacy policies. However, they all have one common purpose. To inform the practices and measures of data collection activities, regulating a legal agreement between the provider of the product or service and the person who wants to use the product or service. This short communication's objective is to reflect on the non-reading of the terms of use in products and services by presenting the ToS;DR as an initiative aimed at user awareness of the terms of use. Users must pay attention to how their data is treated and become aware of initiatives and tools that can help understand the content in terms of use or privacy policies.